Relationship of Confidence with Interpersonal Communication - Diani Maulidya; Yulidar Ibrahim (Universitas Negeri Padang, 2019)
The success of interpersonal communication depends a lot on the quality of one's concepts, both positive and negative. People who lack confidence will tend to avoid communication. This is because a person's confidence can actualize all of his potentials. Therefore the problem to be examined in this study is